The Impact of Digital Currencies on the Financial System and the Social Economy - Wang, Yixuan (International Journal of Global Economics and Management, 2024)
Digital currency, also known as electronic currency or virtual currency, is a type of currency that is not controlled by any central institution or bank. In recent years, blockchain technology has gradually developed and grown, which has attracted wide attention from society. While changing our payment method, its impact on the economy, humanities and other fields can also be seen. As the first decentralized digital currency, the birth of Bitcoin marks the advent of the era of digital currency. With the diversification of the market pattern, the expansion of the transaction scope and the enrichment of the application fields, a variety of digital currencies play a vital role in the social and economic field with their unique advantages. However, how to improve the transaction security of digital currency, improve people's awareness of risk prevention, how to correctly view the advantages and disadvantages of digital currency, and improve the corresponding laws and regulations are all social and economic problems that need to be solved at the present stage.